2000
DOI: 10.1210/jcem.85.10.6846
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretagogue Binding Sites in Peripheral Human Tissues1

Abstract: The family of GH secretagogues (GHS) includes peptidyl (hexarelin) and nonpeptidyl (MK 0677) molecules possessing specific receptors in the brain, pituitary, and thyroid. GHS receptor subtypes have also been identified in the heart; and a gastric-derived peptide, named ghrelin, has recently been proposed as a natural ligand. Our aim was to investigate the presence of GHS receptors in a wide range of human tissues, by radioreceptor assay with [125 I]Tyr-Ala-hexarelin. GHS receptors were detected mainly in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…The presence of GHS-R1a mRNA has been demonstrated specifically in heart and aorta. Both ligand and receptor were found in the myocardium and both ghrelin and peptidyl GHS recognize high affinity binding sites in the heart [45,46]. However it is important to mention that the expression of the GHS-R was only detected by RT-PCR, suggesting that GHS-R is only present at low levels in cardiac tissue.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of GHS-R1a mRNA has been demonstrated specifically in heart and aorta. Both ligand and receptor were found in the myocardium and both ghrelin and peptidyl GHS recognize high affinity binding sites in the heart [45,46]. However it is important to mention that the expression of the GHS-R was only detected by RT-PCR, suggesting that GHS-R is only present at low levels in cardiac tissue.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…In summary, the current opinion still is that the positive influence of GHS on cardiac functions is probably mediated by GHS-R1a. Supportive for this hypothesis are the findings that both ghrelin and GHSs recognize high affinity binding sites in the heart [45]. However, in a separate study, Baldanzi et al [50] demonstrated that the receptor mediating ghrelin actions in cardiomyocytes is not the GHS-R 1a, since this receptor was not localized in cardiomyocytes and both forms of ghrelin (acylated and nonacyl ghrelin, which does not bind to GHS-R 1a) were able to recognize a common binding site.…”
Section: Ghs-r Actions In the Cardiovascular Systemmentioning
confidence: 99%
“…Data regarding the regulation and action of UAG are less consistent (5). The ghrelin receptor is also located in peripheral tissues, indicating direct effects of AG (6). Among these effects, glucoregulatory properties seem to be important (5) and ghrelin-deficient mice developed profound hypoglycemia during calorie restriction (7).…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, ghrelin more closely mimics MK-0677, and it was assumed that the GHSR is the ghrelin receptor. However, evidence has been presented to suggest the existence of receptor subtypes (15). Furthermore, as a 28-aa peptide containing a unique octanoyl modification (11), ghrelin is structurally different from MK-0677.…”
mentioning
confidence: 99%